The assessment of maximal aerobic power with the multistage fitness test in young women soccer players - Castagna, C.; Impellizzeri, F. M.; Manzi, V.; Ditroilo, M. (The Journal of Strength and Conditioning Research, 2010)
The aims of this study were to assess the criterion validity and the accuracy in estimating maximal aerobic power (VO2max) of a popular shuttle running field test (multistage fitness test [MSFT]) in women soccer players. Twenty-six women soccer players (age 12.1 ± 0.9 years, body mass 50 ± 9.2 kg, and height 155 ± 5.7 cm) were tested over separate occasions for VO2max (VO2max test) and MSFT performances with (MSFT peak oxygen uptake) or without (MSFT) gas analysis. Data showed that the VO2max estimation using the MSFT predicting nomogram was significantly lower than MSFT VO2peak (32.7 ± 3.9 vs. 40.1 ± 5.9 ml/kg.min; p < 0.001). No significant difference between VO2max test and MSFT for maximal VO2 and heart rate (HR) was observed (38.7 ± 4.7 vs. 40.1 ± 5.9 ml/kg·min and 203 ± 5.3 vs. 200 ± 9.8 beats/min; p > 0.05; n = 15). The MSFT performance (950 ± 213 m) results significantly correlated with MSFT-VO2peak (r = 0.70; p < 0.001). This study results showed that the MSFT predicting nomogram significantly underestimated VO2peak. Average difference being in the order of 23% of the estimated value. Resulting MSFT-VO2peak significantly related to MSFT performance, and this test may be considered as an indirect measure of individual VO2max in young women soccer players. Furthermore, MSFT may be used as a valid test to assess VO2peak and HRmax when a portable gas analyzer and a HR monitor are available. However, great individual differences may occur. In light of this study results, it is suggested to consider MSFT performance (distance covered) and not estimated VO2max when dealing with young women soccer players.